Brief Cognitive and Behavioral Screening in Children with New-Onset Epilepsy: A Pilot Feasibility Trial - Triplett, Regina L. (Pediatr Neurol, 2014)
BACKGROUND: Minimal work has used psychometrically robust measures in a systematic fashion to identify and monitor children at risk for cognitive and behavioral comorbidities in current epilepsy care. We piloted a computerized cognitive battery and behavioral questionnaire for children with newly diagnosed epilepsy to determine clinical feasibility and acceptability to parents and patients. METHODS: We recruited medication-naïve children (ages 8-17 years) with recent-onset seizures and typical developmental history from the Children's Hospital of Pittsburgh Neurology Clinic. Children completed the CNS Vital Signs computerized battery (CNSVS) while parents completed the Strengths and Difficulties Questionnaire (SDQ). Post-test interviews with parents and patients were completed regarding the acceptability of the assessment procedures. RESULTS: Forty-four families were eligible and 39 agreed to participate (89%). All assessments were completed in less than 45 minutes. Parents rated testing in clinic as convenient and important, expressing strong interest in the cognitive and behavioral impact of epilepsy and medication. Children also rated the testing procedure as acceptable and agreed that they would recommend it to peers. CONCLUSIONS: Our brief battery was tolerated and well-received by children and their parents. Computerized testing of children along with a parent questionnaire is a psychometrically viable approach that is acceptable to families. Our protocol is time-efficient for clinical use with the potential to detect early cognitive and behavioral difficulties related to epilepsy. Ongoing longitudinal study will provide further information regarding the success of our screening methods in monitoring for disease- or treatment-related changes.